Testing of the Granulation Process for the Preparation of a Mixture with the Chemical Composition of a Heavy Tungsten Alloy - Olgierd Janusz GOROCH; Olgierd Janusz GOROCH (Badanie procesu przygotowywania mieszanki o składzie chemicznym wolframowego stopu ciężkiego metodą granulacji, 2020)
The subject of this paper are the results of testing the process of preparation of a granulate made of a mixture of powders with the chemical composition of a heavy tungsten alloy. Different methods of granulation are discussed which reveal how widely they vary in physical and chemical phenomena. It is a testament to how vast the research field of granulation of matter is. The importance and significance of granulation methods were proven with the distinguishing features of the granulated form of the stock materials and products compared to their powdered (dusty) form. Granulation is applied to produce convenient forms of products or intermediates which are acceptable to end users, and to facilitate or even enable the application of products and intermediates in appropriate technologies.
Keywords: Wolframowe stopy cięzkie; Wolframowe stopy cięzkie